Fertility outcome after different treatment modalities of tubal ectopic pregnancy, Observational Study - Reham Refaat Elkhateeb,; Essam Ibrahim Ali,; Ahmed Sameer Abd El-Malek,; Ahmed Mohammed Mahmoud Hasan,; Mohammed Ahmed Ahmed, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective:to assess the impact of expectant, medical, and surgical modalities for the management of tubal ectopic pregnancy (EP) on fertility and reproductive outcomes. Methods:Our study included 159 patients with a history of tubal EP between December 2020 and November 2021 and actively planned to conceive following the EP. They were categorized into three groups: Group A (81 cases), who were treated surgically; Group B (34 cases), who received medical treatment; and Group C (44 cases), who received expectant therapy. They were asked to determine the fertility outcomes after EP, such as the mode of conception, the recurrence of EP, and the occurrence of abortion or live births. All patients who didn’t conceive were subjected to hormonal profile and hysterosalpingography (HSG) evaluation. Results:Among 159 patients, 44 (27.67%) had expectant management, 34 (21.38%) had medical treatment, and 81 (50.94%) had surgical treatment. Regarding the pregnancy outcome after EP, there was a significant difference between the groups (p-value <0.001). The highest clinical pregnancy rate was in the expectant group (72.73%), followed by the medical group (50%) and then the surgical group (34.57%). The tubal damage seen in hysterosalpingography was highest in the surgical group but was insignificant. Conclusions:Expectant treatment was associated with the best reproductive outcome, followed by medical treatment, while surgical treatment had the lowest outcome with an increased risk of tubal complications.